2003
DOI: 10.1034/j.1600-0501.2003.00810.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of platelet, leukocyte, and growth factor levels in point‐of‐care platelet‐enriched plasma, prepared using a modified Curasan kit, with preparations received from a local blood bank

Abstract: The potential use of autologous thrombocytic growth factors to accelerate bone regeneration requires improved methods of isolating platelet-rich plasma (PRP). In addition to discontinuous cell separation, a second method by which PRP is produced at the point-of-care has now become available. In this study, growth factor levels in PRP from these two sources were compared. Whole blood was drawn from 115 healthy donors (73 males, 42 females) aged 21 - 62 years (mean 36, SD 10). The PRP was separated by the blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
123
1
8

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(140 citation statements)
references
References 18 publications
8
123
1
8
Order By: Relevance
“…Apheresis is a more expensive procedure that requires filtration of blood circulating from patient to machine. PRP obtained from apheresis results in a more consistent platelet concentration, typically five times that of whole blood [8].…”
Section: Prp Preparation and Injection Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Apheresis is a more expensive procedure that requires filtration of blood circulating from patient to machine. PRP obtained from apheresis results in a more consistent platelet concentration, typically five times that of whole blood [8].…”
Section: Prp Preparation and Injection Proceduresmentioning
confidence: 99%
“…Likewise, it has been suggested that transforming growth factor-beta (TGF-B), found in higher concentrations with certain preparations, stimulates fibrosis and thus may have a detrimental effect as it may promote greater fibrotic healing of muscle [9]. Apheresis preparations are theoretically less desirable for muscle therapy considering the concentration of PDGF is lower and TGF-B is higher compared to PRP obtained via centrifugation [8].…”
Section: Prp Preparation and Injection Proceduresmentioning
confidence: 99%
“…Mean range of various GF concentrations in PRP preparations, as reported in the literature [22-23, 41-42, 49-51], are summarized in Table 3 . Possibly, a higher platelet count might result in higher TGF-/3 1 levels, whereas higher leukocyte count may lead to higher PDGF-AB levels [50]. The factors influencing GF release still require further study [41] to optimize and standardize clinical benefits from the use of PG.…”
Section: Mode Of Preparation and Quantitativementioning
confidence: 99%
“…A literatura mostra que o PRP obtido por aférese, método utilizado nesse estudo, apresenta uma maior concentração de plaquetas e menor concentração de leucócitos do que o obtido por centrifugação (11) , podendo ser considerado portanto um concentrado de plaquetas mais puro (53) .…”
Section: Discussionunclassified
“…O PRP obtido por aférese possui um volume final maior, maior concentração de plaquetas e menor concentração de leucócitos do que o obtido por centrifugação (11) .…”
Section: Introductionunclassified